Model Pembelajaran Cooperative Script dalam Mendorong Aktivitas Belajar IPA-Fisika - Rahmadani, Wahyu; hurriyah, hurriyah (Natural Science: Jurnal Penelitian Bidang IPA dan Pendidikan IPA, 2019)
This study aims to look at student learning activities using cooperative script models. This is motivated by the lack of optimal implementation of learning using various models, while students tend to be passive and show less interest in learning. Student activity is mainly seen from 2 activities namely writing activities and listening activities. The method used in this study is quasi-experimental methods, the sampling used is cluster random sampling with 2 sample classes. The results showed a significant number of increased student learning activities using this model. The data obtained by the experimental class obtained one very good information (A) for visual activities and one good information (B) for writing activities, while the control class got two good (B ) for both aspects studied. Based on this it can be concluded that student learning activities using cooperative script models have increased when compared with conventional learning